Miradas entre biomédicos y parteras Mayas: el proceso reproductivo femenino - Canto, Judith Ortega (AM. Rivista della Società Italiana di Antropologia Medica, 2010)
Crossing glances: bio-physicians and Mayan midwives around the female reproductive process The paper refers to the socio-cultural construction of representative social actors from two systems of health in relation to the pregnancy-childbirth-puerperium process that begins with the first menstruation and finishes with the menopause. The social representations abstracted by the anthropological analysis, illustrates the labor of this social actors in terms of their group and interpersonal relations, the glance to the women like pregnant bodies or in the childbirth, the elements about self care and prevention which are fundamental, the way to influence in the performance by those who surround to the women and the weight that is granted to the affective life and of relation. The different perspectives between the Mayan therapists and those from Biomedicine and their social role or the ways in that they are working must be considered. The analysis of both groups shows the power position of biomedicine, and to the reasons that explain the importance and resistance of the Mayan folk medicine. Miradas entre biomédicos y parteras Mayas: el proceso reproductivo femenino El artículo refiere a la construcción sociocultural de actores sociales representativos de dos sistemas de salud respecto al proceso de embarazo-parto-puerperio, iniciando con la primera menstruación y terminando con la menopausia. Las representaciones sociales abstraídas del análisis antropológico, ilustran el quehacer de estos actores sociales en términos de sus relaciones interpersonales y grupales, la mirada a las mujeres como cuerpos gestantes o en el alumbramiento, los elementos que sobre autocuidado y prevención son fundamentales, la manera de influir en la actuación de quienes rodean a las mujeres y el peso que se otorga a la vida afectiva y de relación. Las diferencias en el pensamiento entre los terapeutas Mayas y biomédicos, nos trasladan al papel social o tarea que cada medicina tiene. La mirada entre ambos grupos corresponde a la posición de poder de la biomedicina, y a las razones que explican la trascendencia y resistencia de la medicina popular maya.